Feeding Sows with Multi-Species Probiotics During Late Pregnancy and the Lactating Period Influences IgA Concentration in Colostrum and Subsequently Increases the Survival Rate of Piglets in Porcine Epidemic Diarrhea Outbreak Herd - Narathon Innamma; Kampon Kaeoket (Animals)
Porcine epidemic diarrhea (PED) virus is an important cause of diarrhea in sows and piglets [...]